PSV-24 Effect of pre-weaning, post-weaning and fattening growth rate on carcass and meat traits in feedlot Nellore cattle. (5th December 2019) - Amorim, Tamyres; Gemelli, Jessica; Fuzikawa, Ingrid; Martins, Taiane S; Moura, Gabriella; Mueller, Lenise; Ferrinho, Adrielle D; Garbossa, Pollyana; Muñoz, Julian A; Rosa, Caroline; Ramos, Vinicius; Modesto, Raquel; et al.
Abstract: The goal of this study was to evaluate the effect of contrasting growth rate in pre and post-weaning period on carcass traits and meat quality of feedlot Nellore cattle. To high weight gain, in pre and post-weaning period, were be considered management groups with mean weight gain above the third quartile of pre-weaning (PREW) or post-weaning (PROW) weight gain distribution of population to group of moderate gain were be considered management lots with daily average gains between the first and third quartiles of PREW or PROW weight gain distribution of population. In the low gain group will be considered management lots with daily average gains lower than the first quartile of PREW or PROW weight gain distribution of population. We used a total of 500 bulls, registered in the National Association of Breeders and Researchers, fed during 90 days with the same diet, confined and slaughtered. The PREW presented a weight gain rate (WGR) of 57.1, 67.3, and 77.7 kg for low, moderate and high WGR, respectively; and the PROW of 110.3, 113.4, and 119.4 kg for low, moderate and high WGR, respectively. The hot carcass weight influenced WGR in pre-weaning (297.56±11.80, 323.53±10.09, and 364.31±18.88 kg) for low, moderate and high, respectively (P = 0.03). The carcass dressing was affected by weaning period in WGR (pre-weaning: 54.18, 54.33, and 57.88 %; P = 0.034, and post-weaning 55.52, 56.23, and 54.66%; P = 0.471) for low, moderate and high WGR, respectively. The contrasting weight gain groups did not influence the marbling score in PREW (P = 0.128) and PROW (P = 0.772), back fat thickness in PREW (P = 0.719) and PROW (P = 0.833), ribeye area in PREW (P = 0.472) and PROW (P = 0.833), tenderness in PREW (P = 0.936) and PROW (P = 0.911). In general, the gain rate did not improve the carcass traits and meat quality of feedlot Nellore cattle.